Can Erectile Dysfunction Predict Major Cardiovascular Events? - Szekeres Norbert A.; Jeremiás Zsuzsánna; Vida Árpád Olivér; Mártha Orsolya; Porav-Hodade Daniel (Journal of Interdisciplinary Medicine, 2016)
It is estimated that erectile dysfunction (ED) affects more than 150 million people worldwide and this number is expected to double by the year 2025. Vascular component represents the most important etiological cause of erectile dysfunction. ED shares almost all risk factors, such as hypertension, diabetes mellitus, hyperlipidaemia and smoking, with arteriosclerosis. Moderate to severe ED is associated with a considerably increased risk for coronary heart disease (CHD). This review was conducted in May 2016, when the PubMed database was searched using the combination of the terms “erectile dysfunction” and “cardiovascular diseases”, “coronary artery diseases” and “risk factors”. In this review, we analyzed the published literature, regarding the predictive role of ED in CVD and the association of ED risk factors with CVD risk factors, aiming to draw particular attention on the role of sexual inquiry of all men to prevent or decrease major cardiovascular events. In conclusion, the early detection of ED can prevent major cardiovascular events with early management of cardiovascular risk and permits to include patients in a risk stratification group. Erectile function should be evaluated using questionnaires in all male patients to prevent and decrease the rates of major cardiovascular events.